(3GdMhGVQ hfRgI GdNhGWQs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3aEf GdfahS eWHhYI Ydi cQGgI GdeTGb GdeDdeGJ eLHhdI Ydi MH GdJfRgGJ hGdJfbdGJ hbO GSJNQJ Gddg JYGdi aj LeY gPG GdcJGH GdeHGQc eTJedG Ydi dWGFa GdeSQGJ hafhf GdeHQGJ s
(3BNQgG (B:s
(3OYGA ef GdSgQ hQOj hdG fSJYjf HfYeJc EdG Ydi eG JMH jGQH GdeSdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B278 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B648) s
Keywords: (3GdCOHs